Optical signal processing for data error detection and correction using a-SiCH technology - Vieira, Manuel (2019)
In this paper, we explore the nonlinear properties of SiC multilayer devices under UV irradiation to design an optical processor for error detection and correction, that enables reliable delivery of spectral data of four-wave mixing over unreliable communication channels. The SiC optical processor for error detection and correction is realized by using a SiC pin/pin photodetector with UV biased optical gating elements. The relationship between the optical inputs and the corresponding digital output levels is established. Data shows that the optical bias act as a selector that picks one or more states by splitting portions of the input multi optical signals across the front and back photodiodes. Boolean operations are demonstrated optically, additional parity logic operations are performed and checked for errors together. As an example we describe an all-optical processor for error detection and correction and then, provide an experimental demonstration of this fault tolerant reversible system. An intuitive representation with a 4 bit original string coloured message and the transmitted 7 bit string, the parity matrix, the encoding and decoding processes and the design of SiC syndrome generators are presented.